COST ANALYSIS AND MALARIA THERAPY FOR HOSPITALIZED PATIENT IN RSUD ULIN BANJARMASIN KALIMANTAN SELATAN 2006‐2009 PERIOD - Noor Hafizah; Mustofa Mustofa (Faculty of Pharmacy, Universitas Gadjah Mada)
Malaria is still become one of a serious health problem in Indonesia especially in Kalimantan and other island except Java and Bali. South Kalimantan is one of the endemic province of malaria. Malaria problem is not only about the healthcare, but also concern about the economic problem. economic problem can occured because of cost of healthcare, especially when patient have to hospitalized, and the lost of productivity during the illness. The purpose of this research is to know any component and direct medical cost that patient have to pay when patient had a health care during opname. This research is also to observe therapy guidelines in RSUD Ulin Banjarmasin South Kalimantan. This research used a descriptive non experimental method. Sample wass collected retrospectively from medical record of patients who hospitalised in 2006‐2009 and finance departement to know how much the cost that patient have to spend. Cost of therapy in malaria patient without complication for VIP, Utama, I, II, and III was Rp 6.010.736,00; Rp 3.345.877,00; Rp 1.531.057,00; Rp 2.384.985,00; dan Rp 1.919.354,00 and in malaria patient with complication for Utama and III was Rp 3.993.575,00 dan Rp 3.160.617,00. Average cost of therapy in malaria patient with complication was higher than malaria patient without complication. The component of therapy cost was drug therapy cost and nondrug therapy cost, including hospitalising cost, medical action cost, supporting cost, and administration cost. The evaluation of malaria therapy in complication and non complication patient shows that not all of antimalaria and antimalaria dosage which were used inRSUD Ulin Banjarmasin was according to DEPKES RI guidelines in 2003. Keywords: malaria, direct medical cost, therapy evaluation